2019
DOI: 10.1016/j.jad.2018.11.055
|View full text |Cite
|
Sign up to set email alerts
|

The association between child and adolescent depression and poor attendance at school: A systematic review and meta-analysis

Abstract: Background: Depression in young people may lead to reduced school attendance through social withdrawal, loss of motivation, sleep disturbance and low energy. We systematically reviewed the evidence for an association between depression and poor school attendance.Methods: Seven electronic databases were searched for quantitative studies with school-aged children and/or adolescents, reporting a measure of association between depression and school attendance. Articles were independently screened by two reviewers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
96
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 149 publications
(103 citation statements)
references
References 47 publications
4
96
2
1
Order By: Relevance
“…All four measures of emotional disorder/difficulties were associated with an increased risk of all three types of school absence. These findings were in line with our expectations and previous evidence [14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…All four measures of emotional disorder/difficulties were associated with an increased risk of all three types of school absence. These findings were in line with our expectations and previous evidence [14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 94%
“…Although 18 (26.5%) of the 68 children with depression in this sample also had a conduct or oppositional disorder, the majority of them did not, and thus it is unlikely that the association between depression and unauthorised absence is simply a result of comorbid behavioural disorders. These findings are also in line with a recent systematic review that reported particularly strong evidence with regard to depression and unexcused absence or truancy [17].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, this paper focuses on associations between anxiety and school attendance, and findings for associations with depression and internalising problems (i.e. combined symptoms of anxiety and depression) are reported elsewhere (Finning, In preparation; Finning et al., ). Understanding the role of anxiety in relation to poor school attendance is important in order that children with anxiety can be identified quickly, and appropriate interventions implemented.…”
Section: Introductionmentioning
confidence: 99%
“…School refusal is typically considered to be related to internalising problems such as depression or anxiety, while truancy is considered to be related to externalising problems. However, a study by Egger, Costello, and Angold (2003) demonstrated that school refusal and truancy are not mutually exclusive, and other studies, including two linked systematic reviews, have shown that truancy is strongly associated with internalising problems (Finning et al 2019a(Finning et al , 2019bMandalia et al 2018;Gase et al 2014). It could therefore be argued that grouping attendance problems into subtypes such as school refusal and truancy lacks empirical support, and may result in adults around the young person making inaccurate assumptions about the underlying aetiology of the problem.…”
Section: Introductionmentioning
confidence: 99%